2013
DOI: 10.1038/cdd.2013.119
|View full text |Cite
|
Sign up to set email alerts
|

HINCUTs in cancer: hypoxia-induced noncoding ultraconserved transcripts

Abstract: Recent data have linked hypoxia, a classic feature of the tumor microenvironment, to the function of specific microRNAs (miRNAs); however, whether hypoxia affects other types of noncoding transcripts is currently unknown. Starting from a genomewide expression profiling, we demonstrate for the first time a functional link between oxygen deprivation and the modulation of long noncoding transcripts from ultraconserved regions, termed transcribed-ultraconserved regions (T-UCRs). Interestingly, several hypoxia-upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 49 publications
2
78
0
1
Order By: Relevance
“…Furthermore, the presence in the putative uc.63 promoter region at 5′ of XPO1 gene [23] of hypoxia-inducible factor (HIF) candidate binding sites, which may drive uc.63 expression in hypoxic conditions, further confirm the same transcription orientation.…”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, the presence in the putative uc.63 promoter region at 5′ of XPO1 gene [23] of hypoxia-inducible factor (HIF) candidate binding sites, which may drive uc.63 expression in hypoxic conditions, further confirm the same transcription orientation.…”
Section: Resultsmentioning
confidence: 90%
“…Although >200 bp each, the T-UCRs are distinct and unlike lncRNAs show an extreme sequence conservation between the orthologous regions of human, mouse and rat genomes (Bejerano et al, 2004b; Calin et al, 2007). As the T-UCRs resisted mutations during evolution, these regions of the genome and the RNAs they encode are thought to play essential life functions such as tissue-specific regulation of gene expression (Ferdin et al, 2013; Pennacchio et al, 2006). Interestingly, the host genes and the nearest up- and down-stream genes of many T-UCRs are known to be involved in transcription and RNA splicing (Bejerano et al, 2004a,b, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot generalize that all T-UCRs are not functional as many recent studies showed altered T-UCR expression profiles in different types of cancers which might be associated with carcinogenesis in neuroblastoma, leukemia, hepatic, prostate and colorectal cancers (Braconi et al, 2011; Calin et al, 2007; Hudson et al, 2013; Mestdagh et al, 2010; Pauli et al, 2011; Sana et al, 2012; Scaruffi, 2011). Interestingly, many T-UCRs are also shown to be induced under HIF-1 regulation when tumor cells were subjected to hypoxia (Ferdin et al, 2013). Cerebral hypoxia and ischemia are known to rapidly alter the expression of ncRNAs including miRNAs, piRNAs and lncRNAs with significant impact on the post-stroke functional outcome (Dharap et al, 2009; Dharap et al, 2011, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of vlincRNAs serve as hallmarks of pluripotency and cancer [88]. lncRNAs transcribed from non-coding ultraconserved regions are involved in many biological functions including hypoxia response [89] and regulation of pri-miRNA processing [75] and are also being studied as thereapeutic targets and diagnostic tools in cancer. The current cancer applications are mostly based on manipulating lincRNAs [reviewed in 90].…”
Section: Therapeutic Aspects Of Lncrnasmentioning
confidence: 99%